Studi Deskriptif tentang Pola Asuh Otoritatif, Kontrol Diri, dan Sikap Remaja Terhadap Perilaku Seks Bebas - Dwi Adhinda Junaidi Putri (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2019)
Adolescent`s attitude will affect the way they behave. Adolescent`s attitude toward free sex is the degree to which the adolescent accept or refuse the various forms of sexual behavior carried out by a couple who are not bound in the bonds of marriage. Authoritative parenting and self-control is a factor that are factors that may have influenced the adolescent`s attitude towards free sex. This study aimed to describe: (1) the level of applied authoritative parenting, (2) the level of adolescent`s self-control, and (3) the level of adolescent`s attitude towards free sex. This study used quantitative approach by using descriptive method. The population of this research were 303 students at SMAN 1 Stabat growing with authoritative parenting. By using proportional stratified random sampling technique, 172 students were chosen as the samples. The instrument of the research was a scale. The purpose of the research was analyzed by using hypothetic mean. The results of the research revealed that: (1) the authoritative parenting applied by parents was in fairly adequate category, (2) the adolescent`s self-control was in adequate category, (3) the adolescent`s attitude towards free sex was in reasonably refused category.